(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article shows the relationship between the real person and the image of the author in a creation of literature. Especially, it reveals importantly autobiographical literature, where the author and protagonist as close as possible to one another, but in most cases are not identical. While analyzing the poem, it occurs the problem of genre specification and ratio of the author and the hero of «Black Arab». The poem constructed on on the autobiographical basis, it has two narrative plans – the plan of the present (atthis level the narrator acts) and the past (where the narrative is reconstructed on author’s own «I»). It isdistinctly seen the split of the subject. On the one hand, it may imply a certain detachment from the author himself from the present and the past. On the other hand, the autobiographical creation assumes the coincidence of the author and the hero. The author endowed his hero with his own biography, destiny and character. Thus, it was analyzed that the author did not copy the mirror reflection of his personality. It seems that he grasped his biography and did not copy the reality directly, but creatively transforms it. Moreover, in this paper it identifies the most important dominant of the author’s consciousness : monologics, «right-evaluative point of view» (by B. Corman), passeism and phenomenological nature of the narrative.